What Teachers Need in Implementing Environmental-Based Learning in The Elementary School - Anastasia Baan (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
Much research explained that environmental-based learning contributes significantly to learning quality, but many teachers have not implemented it in the learning process yet. Therefore, this study aimed to describe what teachers need in the implementation of environmental-based learning in the learning process in elementary schools. This study used a quantitative and qualitative design that involved 16 teachers from four elementary schools as research participants. The research data, in the form of nominal data, was collected through a questionnaire, document analysis, and checklist, while verbal data about the problem in implementing environmental-based learning by interview. Nominal data were analyzed by simple statistical analysis techniques, while verbal data was analyzed by following the steps: reduction, classification, categorization, presentation, interpretation, and conclusion. The findings showed that in implementing environmental-based learning, teachers faced many problems caused by internal and external factors, which include the lack of teachers' experience, unavailable sources of information and examples as references, media and facilities available in schools, and policy factors. Teachers needed technical guidelines, workshops/training, and learning media of the learning model to improve their learning. These findings are significant as a basis for policy-making in increasing the learning quality. In addition, these findings lead to an analysis of school needs in developing learning quality.